EFEKTIVITAS DANA OTONOMI KHUSUS DALAM MENJAWAB KEBUTUHAN MASYARAKAT ASLI PAPUA DI KABUPATEN BIAK NUMFOR - Jemmi Burdam; Beatus Mendelson Laka (Sekolah Tinggi Pariwisata Mataram, 2022)
The balance of the Special Autonomy Fund for Papua Province and regencies/municipalities in the context of accelerating development in Papua in various sectors will be realized if its management is in accordance with the principles of people's welfare and monitoring mechanisms that are in accordance with the principle of expediency. This study aims to identify and explain the suitability of the balancing regulation of the Papua Province Special Autonomy Fund with the principles of people's welfare and the benefits of the monitoring mechanism for the allocation of the Papua Province Special Autonomy Fund by the Papua Provincial Government. With the end of the special autonomy fund in 2021, it is necessary to evaluate the use of the special autonomy fund. On the other hand, many people expressly refuse to continue because people think that the special autonomy fund has failed and has caused polemics in the indigenous Papuan community. Many Papuan academics say that the special autonomy funds are not effective because there are no derivative rules from government regulations related to special autonomy. The management of the Papua Province Special Autonomy Fund has not met the principles of the welfare state, because the distribution is greater for the Province than for the Regency/City. The mechanism for monitoring the utilization of the Special Autonomy Fund has not guaranteed the fulfillment of the principle of benefit. The absence of a Papuan Governor's Regulation on Special Task Forces and on program selection criteria and the lack of a supervisory role from a special Papua Province institution as a form of external supervision. So that it becomes a polemic among the indigenous Papuans, especially in the Biak Numfor district. This research is a normative juridical research that wants to identify from the legal aspect. The data used consists of primary legal materials, secondary legal materials, and tertiary legal materials. The research method used is normative juridical research which aims to examine the legal aspects related to the procedures for managing and supervising the Papua Special Autonomy Fund between Provinces and Regencies/Cities. The location of this research is Biak Numfor Regency. The subjects of this study were the Chairperson of the DPRD Biak Numfor Regency, Milka Rumaropen, and the Chairperson of the Customary cloth kankanra Byak, Biak Numfor Regency. Mr. Yarangga, as well as the Papuan people, are in the Numfor breed district. In determining the research subject, a purposive sampling was used. The sampling technique is not based on probability, but is chosen to describe the juridical situation related to the problem under study, or the sample aims to create key informants, then the sample is determined on a rolling basis according to the research needs or the data required. The analysis technique used in this research is carried out with a flow that includes data reduction, data presentation, and verification stage. The verified data from this research are in the form of expressions or words, descriptions of field facts which are entirely obtained from informants, observation sheets and documents from the Papua Province Special Autonomy Fund. the traditional head of the Biak Territory.